2023
DOI: 10.1159/000534244
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Cachexia Index Can Be Used to Prognostically Predict Patients with Gastric Cancer Undergoing Gastrectomy

Katsunobu Sakurai,
Naoshi Kubo,
Tsuyoshi Hasegawa
et al.

Abstract: Objective. Cancer cachexia occurs in cancer patients more frequently as the cancer progresses, with a negative impact on treatment outcomes. In this study, we sought to clarify the clinical impact of a cancer cachexia index CXI in patients with gastric cancer (GC) undergoing gastrectomy. Methods. Between January 2013 and December 2018, we reviewed data from 556 patients treated for GC at our hospital. CXI was calculated using skeletal muscle index (SMI), serum albumin, and neutrophil-lymphocyte ratios (NLR). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previous analyses by Gong et al . 18 and Sakurai et al 19 evaluated CXI in cohorts of patients who underwent surgical resection of gastric cancer, and both identified low CXI as an adverse predictor of survival. The present study has shown that this negative effect is also evident in oesophageal cancer, and in cohorts treated with NAC before planned surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses by Gong et al . 18 and Sakurai et al 19 evaluated CXI in cohorts of patients who underwent surgical resection of gastric cancer, and both identified low CXI as an adverse predictor of survival. The present study has shown that this negative effect is also evident in oesophageal cancer, and in cohorts treated with NAC before planned surgical resection.…”
Section: Discussionmentioning
confidence: 99%